Validation of administrative database codes for acute kidney injury in kidney transplant recipients. Issue 1 (December 2016) - Molnar, Amber; van Walraven, Carl; McArthur, Eric; Fergusson, Dean; Garg, Amit; Knoll, Greg
Abstract Background Validation studies of acute kidney injury (AKI) diagnostic codes performed in the general population have shown poor sensitivity, but the accuracy of such codes in the kidney transplant population remains unknown. Objective The objective of this study is to determine the accuracy of AKI diagnostic codes in kidney transplant recipients. We hypothesized that the sensitivity of diagnostic codes would be significantly greater in the kidney transplant population since these patients are closely followed by nephrologists and are more likely to have serum creatinine measured. Design The design is a population-based retrospective cohort study using healthcare administrative and laboratory databases. Setting The setting is in Southwestern Ontario and Ottawa, Ontario, Canada, from 2003 to 2012. Patients We included first-time kidney transplant recipients admitted to hospital for whom serum creatinine was measured in hospital and within 6 months prior (n = 524). Methods Patients meeting the Acute Kidney Injury Network (AKIN) classification serum creatinine change criteria were classified as having AKI. We determined the sensitivity, specificity, and negative and positive predictive values for theICD-10 -CA code for AKI when present as an admission diagnosis, most responsible diagnosis, or any diagnosis compared to a reference standard of AKI defined by the AKIN criteria (stage 1 or greater, stage 2 or greater, or stage 3). Results Forty-five percent of included kidney transplant patients had a diagnosis of AKI. The most sensitive coding algorithm (reference standard AKIN stage 2 or greater, ICD- 10 code present as any diagnosis) had a sensitivity of 42.1 % (95 % CI 31.7, 53.3), a specificity of 90.6 % (95 % CI 87.6, 93.0), and a positive likelihood ratio of 4.5. The median (IQR) rise in serum creatinine from baseline in patients with and without AKI codes was 104 (57 to 158) μmol/L and 16 (−3 to 41) μmol/L, respectively (Mann-Whitney test, p < 0.0001). Limitations The low sensitivity of the AKI code may be due to an alternative diagnosis of acute rejection being assigned in certain cases. The cause of AKI could not be determined. Conclusions Similar to the general population, theICD-10 N17x code misses many kidney transplant patients with AKI during their hospitalization. This makes the code unusable for studying the incidence and consequences of AKI in hospitalized kidney transplant patients. Abrégé Mise en contexte Les études de validation portant sur les codes diagnostiques pour l'identification de l'insuffisance rénale aiguë (IRA) menées dans la population générale ont révélé une piètre sensibilité de détection de ceux-ci. Toutefois, leur fiabilité chez les patients ayant subi une greffe du rein reste à démontrer. Objectif de l'étude Cette étude visait à évaluer la précision des codes de diagnostic de l'IRA chez les patients ayant reçu une greffe rénale. Le postulat de départ était que la sensibilité de ces codes serait nettement supérieure au sein de cette population puisque ces patients bénéficient d'un suivi par un néphrologue et sont plus susceptibles de voir leur taux de créatinine mesuré régulièrement. Cadre et type d'étude Il s'agit d'une étude de cohorte rétrospective, représentative de la population. Elle a été réalisée entre 2003 et 2012, à Ottawa et dans le sud-ouest de l'Ontario, à partir de bases de données de laboratoire. Participants Un total de 524 receveurs d'une première greffe rénale ayant été hospitalisés et dont la créatinine a été mesurée au moment de l'hospitalisation et dans les 6 mois précédant celle-ci. Méthodologie Les patients dont le taux de créatinine correspondait aux stades de classification de l'IRA duAcute Kidney Injury Network (AKIN) ont été considérés en insuffisance rénale aiguë. Des valeurs de spécificité et de sensibilité ainsi que des valeurs de prédiction positives et négatives pour le codeICD-10 -CA en situation d'IRA ont été déterminées lorsque l'IRA constituait le diagnostic d'admission, le diagnostic le plus probable mis en cause, ou n'importe lequel des diagnostics évoqués, en comparaison avec les standards de référence définis par les critères de l'AKIN (stade 1 ou supérieur, stade 2 ou supérieur, ou stade 3). Résultats Au total, 45 % des patients admis dans cette étude ont reçu un diagnostic d'IRA. L'algorithme de codage le plus sensible [stade 2 en référence aux standards AKIN avec pour tout diagnostic la présence du codeICD-10 -CA] présentait une sensibilité de 42, 1 % [95 % IC 31, 7 à 53, 3], une spécificité s'élevant à 90, 6 % [95 % IC 87, 6 à 93, 0] et un rapport de vraisemblance positif de 4, 5. La hausse médiane [étendue interquartile] de créatinine sérique par rapport aux valeurs de base était de 16 [-3 à 41] μmol/L pour les patients non codés et de 104 [57 à 158] μmol/L pour les patients chez qui on décelait le codeICD-10 -CA [test de Mann-Whitney, p < 0, 000 1]. Limite de l'étude Dans certains cas, la faible sensibilité du codeICD-10 -CA pourrait s'expliquer par un code de rejet aigu. Les causes d'épisodes d'IRA n'ont pas pu être établies dans cette étude. Conclusions À l'instar de l'ensemble de la population, le codeICD-10 N17x sous-estime l'incidence de l'IRA chez les greffés rénaux lors d'une hospitalisation. Ceci rend l'utilisation de ce code peu propice à des fins d'études sur l'incidence et les conséquences de l'IRA chez les patients hospitalisés qui ont subi une greffe du rein.